2019
DOI: 10.12659/msm.918517
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Titanium Scaffolds Enhance Osteogenic Differentiation and New Bone Formation by Cultured Adipose Tissue-Derived Stem Cells Through the IGF-1R/AKT/Mammalian Target of Rapamycin Complex 1 (mTORC1) Pathway

Abstract: Background: This study aimed to investigate the effects of three-dimensional (3D) printed titanium (3DTi) scaffolds on osteogenic differentiation and new bone formation by 3D cultured adipose tissue-derived stem cells (ADSCs) in vitro, and the effects of bone regeneration in vivo using a full-thickness mandibular defect rat model, and the mechanisms involved. Material/Methods: Alpha-beta titanium alloy (Ti6Al4V) 3DTi scaffolds were prepared with Cellmatrix hydrogel and 3D culture medium. ADSCs were impregnated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Thus, the methodology of IGF-1 supplementation is highly promising for engineering de novo vasculature in tissue regeneration [81]. Three-dimensional (3D) culture of mesenchymal stem cells with 3D titanium scaffolds enhances osteogenic differentiation and new bone formation through the IGF-1R/AKT/ mTORC1 pathway [82]. This method of osteointegration may have clinical application in the preparation of bone grafts before implantation to improve the repair of mandibular bone defects [82].…”
Section: Osteocytes Governing Bone Regenerationmentioning
confidence: 99%
“…Thus, the methodology of IGF-1 supplementation is highly promising for engineering de novo vasculature in tissue regeneration [81]. Three-dimensional (3D) culture of mesenchymal stem cells with 3D titanium scaffolds enhances osteogenic differentiation and new bone formation through the IGF-1R/AKT/ mTORC1 pathway [82]. This method of osteointegration may have clinical application in the preparation of bone grafts before implantation to improve the repair of mandibular bone defects [82].…”
Section: Osteocytes Governing Bone Regenerationmentioning
confidence: 99%
“…Our previous studies demonstrated that IGF-1R has a crucial impact on the osteo/odontogenic differentiation of DPSCs and SCAPs ( Shu et al, 2016 ; Liu et al, 2018 ). Similarly, numerous studies have shown that the activation of IGF-1/IGF-1R can regulate cell senescence and osteogenesis, participate in maintaining intracellular homeostasis, and promote tooth-related tissue regeneration ( Sergi et al, 2019 ; Zhou et al, 2019 ). This study explores the role of lncRNA ANRIL/miR-7-5p/IGF-1R axis in the osteogenic differentiation of inflamed periodontal ligament stem cells for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that topological modification could significantly influence the porous properties to a greater extent than the material type (37). Also, Zhou et al (38) verified the osteogenic effect of 3D scaffold-based scaffold on adipose stem cells and confirmed that its mechanism was related to the IGF-1R/ protein kinase B (AKT)/Mammalian Target of Rapamycin Complex 1 (mTORC1) cell signaling pathway.…”
Section: Surface and Three-dimensional (3d) Structure Transformationmentioning
confidence: 97%